Modellus software in the learning of kinematics in engineering students (LACCEI, 2024)
This research aims to determine the effect of the application of Software Modellus in the learning of kinematics in students of Industrial Engineering of a Peruvian private university. Using a pre- and post-test experimental design, the Kinematics Graph Comprehension Test (TUG-K) was applied to 68 students during a training period and the level of learning achieved was determined using the Hake factor. The results were analyzed using the Shapiro-Wilk and Mann-Whitney U tests. The study showed that the application of Modellus significantly improves the learning of kinematics in the experimental group, obtaining a medium level for the Hake index (p ≤ 0.05), but regarding gender, better results were evidenced in the women of the experimental group (96%) than in the men. As for the results according to the "registration" variable, 95% of students who attend for the first time took advantage of the use of the software while second and third-enrollment students took advantage of it 100%. It is concluded that there is a significant increase in the average level in the learning of kinematics by applying the Modellus Software compared to traditional teaching with better results in female students and in first-enrollment students. It is recommended to implement the proposal in laboratory practices, form mixed groups and develop hybrid guides.